Demographic Study to Evaluate the Morbidity Status of Children in Jodhpur City (International Journal of Ayurveda and Pharma Research, 2024)
Every nation's foundation is its children, and that nation's top priority is to ensure their health. Their early years of life are characterized by their development and growth. The first few years of life are the most important time because of the fast growth and development that is common at this age and necessitates ongoing observation. During this time, roughly 40% of physical growth and 80% of mental development take place. Any obstacle they face at this age could severely restrict their ability to develop and grow. A child who lacks access to health care during these formative years is denied the chance to develop into a healthy adult, and the harm caused in the early years may be permanent or in the long run. Children under the age of five continue to die from ailments that are treatable or preventable. Despite the significant progress in immunization to strengthen the immune system, medical research has not yet developed a fully effective defense against virulent organisms, and occasionally we fail in the struggle for survival. To understand the primary causes of death and the carers' patterns of seeking medical attention before the deaths of such children, a cross-section study encompassing the area of Jodhpur, Rajasthan, was done. The survey was conducted on 1000 children living in the surroundings of the Post Graduate Institute of Ayurved, Dr. S. R. Rajasthan Ayurved University, Jodhpur. Demographic studies show that Respiratory tract Infection is the main cause of morbidity in children. In Respiratory tract Infection recurrent cough, recurrent running nose, recurrent nasal obstruction, recurrent sore throat, and breathlessness are included. Out of which maximum number of children suffered from recurrent running nose.